The human rights based approach and the United Nations systems (United Nations Educational Scientific and Cultural Organization (UNESCO), 2006)
This study brings together the expreiences of different UN agencies, programmes and bodies, undertaken with a view to integrating human rights in their action. The study looks into policies and practices endorsed throughout the UN reform in 1997.